Innovative Methods in Teaching ESP - Umirxon Odilovna Azimova (Web of Journals Publishing, 2023)
This article aims to discuss the basic concepts of the ―English for Specific Purposes‖ (ESP) approach to language teaching in higher education institutions, its features, impact of methodology and describes the selection of teaching materials based on learners‘ specific needs, the role of teachers and students in this process and difficulties related to teacher, student, environment and others in teaching English for Specific Purposes.
Keywords: basic concepts, ESP; language teaching, methodology, teaching materials, learners ‘specific needs.